Strategi Pengelolaan Hotel Berbasis Kearifan Lokal dalam Mendukung Pariwisata Berkelanjutan di Sumatera Utara - Afni, Riza; Tambunan, Susi Marta; Manurung, Rianto; Sinay, Kaleb Yusuf (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze hotel management strategies based on local wisdom to support sustainable tourism in North Sumatra. Local wisdom, as a cultural value that lives in the community, has great potential in creating service differentiation and increasing the competitiveness of the sustainability-oriented hotel industry. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation at several hotels that implement elements of local wisdom in their operations. Data analysis was conducted using thematic analysis techniques to identify the applied strategy patterns. The results show that hotel management strategies based on local wisdom can be realized through the integration of cultural values ​​in architectural design, the provision of regional culinary specialties, culture-based services, and empowerment of local communities. The implementation of these strategies has been proven to increase tourist satisfaction, strengthen destination identity, and support economic, social, and environmental aspects within the framework of sustainable tourism. However, challenges faced include limited human resources, a lack of standardization of the application of local wisdom, and minimal integrated policy support. This study implies that synergy between hotel industry players, the government, and local communities is essential to optimize the application of local wisdom as a sustainable hotel management strategy. These findings are expected to be a reference for policies on the development and implementation of hotel management that supports sustainable tourism in Indonesia.